(untitled) - Gower, Roger (London, 1995)
The book covers managing the class; managing equipment and using material; developing skills; presenting and practising language; giving feedback and planning lessons.
Keywords: English language,English language,Language and languages; Study and teaching,Textbooks for foreign speakers,Study and teaching